"Je lis ça comme je lirais un roman": Reading Scientific Works on Hypnotism in Late Nineteenth-century France. Issue 3 (November 2016) - Hajek, Kim M.
Abstract : In France ca. 1878–1890, hypnotism enjoyed unprecedented legitimacy and cultural authority, with literary interest flourishing alongside medico-scientific enquiry into the topic. In light of these dual conditions, this article examines how texts about hypnotism constituted their ideal reader, with a focus on the role of the reader's imagination. It firstly elucidates the ways scientific texts guided their ideal reader to suppress any imaginative response to hypnotic phenomena. If this served to neutralize potentially damaging interpretations of phenomena, it also placed constraints on scientific experimentation into hypnotism. Fictional studies of hypnotism raised the possibility, however, that it was valid to read accounts of hypnotic phenomena "like novels", that is, in an imaginative mode. The analysis, in this second part, centres on an episode from Jules Claretie's 1885 novel Jean Mornas, before finally exploring the implications for scientific enquiry of fluidity between scientific and literary ways of reading hypnotism.